Strain manipulation of the polarized optical response in two-dimensional GaSe layers. Issue 6 (5th February 2020) - Zhou, Jiangpeng; Wu, Yaping; Wang, Hao; Wu, Zhiming; Li, Xu; Yang, Weihuang; Ke, Congming; Lu, Shiqiang; Zhang, Chunmiao; Kang, Junyong
Abstract : Considerable enhancements of room temperature circular polarization and anisotropic optical response in 2D GaSe are achieved through the strain manipulation. Abstract : We report tunable optical performances of gallium selenide (GaSe) layers in phonon vibrations, band edge emission, circular polarization, and anisotropic response via strain manipulation. By applying a uniaxial tensile strain, frequency shift and peak broadening are observed in Raman spectra. A shrink in bandgap is demonstrated in photoluminescence (PL) spectra and confirmed by first-principles calculations. A continuously growing circular polarization from 3.8% to 37.9% is detected at room temperature when the tensile strain is increased from 0% to 0.35%, which is almost a ten-fold enhancement compared with that under the non-resonant excitation. Through the theoretical calculations, the decrease in exciton lifetime is revealed to be responsible for the overwhelming enhanced circular polarization. By deforing the lattices of GaSe layers, the Raman intensity was found to be suppressed in the strain direction. The intrinsic fourfold-symmetry of the E2g 1 mode in angle-dependent Raman spectra is tuned to a two-fold symmetry. An anisotropic PL response is further regulated by changing the structural symmetry of GaSe lattices. A maximal polarization of 66.0% is achieved when the detection polarizations are perpendicular to the strain direction. All the findings in this study suggest a route for tuning the optical properties, particularly the polarized response in two-dimensional (2D) materials, and provide a strategy for developing flexible and anisotropic 2D optical devices.